2020
DOI: 10.3390/w12061609
|View full text |Cite
|
Sign up to set email alerts
|

Multipurpose Use of Artificial Channel Networks for Flood Risk Reduction: The Case of the Waterway Padova–Venice (Italy)

Abstract: Many rivers are increasingly threatened by extreme floods, and effective strategies for flood risk mitigation are difficult to pursue, especially in highly urbanized areas. A flexible and multipurpose use of the complex networks of artificial channels that typically cross these regions can play a role in flood risk mitigation. A relevant example concerns the possible completion of a waterway from Padova to the Venice Lagoon, in North-Eastern Italy. Once completed, the waterway can boost shipping (which is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…In this study, we propose a simplified method based on the implementation of Goda's formula directly on the domain, avoiding the 2D modeling of the barrier but keeping the high accuracy of the results. Similar approaches are widely implemented into mathematical models available in the literature by developing a set of specific links to reproduce the presence of long and narrow structures, such as sills and levees [63][64][65][66].…”
Section: Submerged Breakwatersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we propose a simplified method based on the implementation of Goda's formula directly on the domain, avoiding the 2D modeling of the barrier but keeping the high accuracy of the results. Similar approaches are widely implemented into mathematical models available in the literature by developing a set of specific links to reproduce the presence of long and narrow structures, such as sills and levees [63][64][65][66].…”
Section: Submerged Breakwatersmentioning
confidence: 99%
“…The hydrodynamic of the barrier is solved by the HD and SW modules, without any change in bottom elevation, by disabling the use of the sedimentological model. implemented into mathematical models available in the literature by developing a set of specific links to reproduce the presence of long and narrow structures, such as sills and levees [63][64][65][66].…”
Section: Submerged Breakwatersmentioning
confidence: 99%
“…In addition, Wang et al (2019) examined the impacts of interbasin water diversion on flood control and drainage processes in a waterreceiving lake basin in China using the MIKE model. Subsequently, Mel et al (2020b) identified the optimal floodgate operation rules for diverting floodwater in the Bacchiglione-Brenta river network in Italy, using the 2DEF hydrodynamic model; they also evaluated the applicability of those rules (Mel et al, 2020a). Although the use of hydrodynamic models to simulate floodwater diversion has greatly clarified the effects of such operations on flood risk reduction, these studies have mainly considered the relationships between regional flood characteristics and associated diversion canal operation schemes, which have limited global applicability as well in other regions.…”
Section: Introductionmentioning
confidence: 99%
“…A significant point in the above studies is the optimal redesign of the flood control canal capacities in rehabilitation projects. However, since in many dense urban areas, the total renovation of the drainage canal network, widening or deepening, is limited by financial and spatial constraints, identifying the problematic canals and locally redesigning and renovating them is a practical and effective option (Mel et al 2020). Therefore, using optimization tools to locally redesign the canals by considering flood probability as the constraint allows for the maximum flow capacity for flood discharge with the minimum reconstruction cost.…”
mentioning
confidence: 99%